Reclaiming the Right to Self-Determination: Aisyiyah Progressive Womanhood - Siti Syamsiyatun (Islamica: Jurnal Studi Keislaman, 2022)
The notion of womanhood has become a serious concern of most cultures, religions and states. As such can be seen in written documents they have produced to educate and discipline their female subjects. However, most of the documents are produced by male authority within their respective fields; and many propagated for submissive womanhood. Why these male authors do so? Why they tend to discipline women? Where are the voices of women? These are the questions that attracted me to do research. To start with, I do research on Aisyiyah’s ideas on womanhood, because it is an Islamic organization for women that has survived more than a century. This is qualitative research with mixed methods in the data collection. The primary data comes from published documents and interviews. The research finds that these Aisyiyah women are strategic in developing their idea of womanhood; they take up the opportunity from learning to reclaim the right to self-identification as progressive woman, not submissive and inactive women as proposed in other books. Aisyiyah build its argumentation based on theological, scientific as well as cultural considerations. They also collaborate with other partners of similar minds to sustain their vision on womanhood.